2004
DOI: 10.1080/00071660410001668905
|View full text |Cite
|
Sign up to set email alerts
|

Linear regression approach to study amino acid digestibility in broiler chickens

Abstract: 1. An experiment was conducted to investigate whether a linear regression approach is a suitable tool for determining the amino acid (AA) digestibility up to the terminal ileum of broiler chickens. Solvent-extracted rapeseed meal (RSM) was used as the model ingredient. 2. Ten diets with 5 different inclusion rates of RSM (60, 120, 180, 240 and 300 g/kg, corresponding to crude protein concentrations from 170 to 250 g/kg in the diet), each without or with a supplementation of phytase (500 U/kg), were fed ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 16 publications
7
98
0
6
Order By: Relevance
“…A mixed microbial fraction was isolated from the liquid effluent by differential centrifugation according to Boguhn et al (2006), freezedried and ground. Amino acid (AA) concentrations in the microbial fraction were measured as described by Rodehutscord et al (2004). The concentrations of tryptophan, histidine and tyrosine were not determined.…”
Section: Digestibility and Energy Concentrationmentioning
confidence: 99%
“…A mixed microbial fraction was isolated from the liquid effluent by differential centrifugation according to Boguhn et al (2006), freezedried and ground. Amino acid (AA) concentrations in the microbial fraction were measured as described by Rodehutscord et al (2004). The concentrations of tryptophan, histidine and tyrosine were not determined.…”
Section: Digestibility and Energy Concentrationmentioning
confidence: 99%
“…Rodehutscord et al (2004) found that supplementing phytase did not improve the ileal AA digestibility of CM, as determined by the regression method with practical CP levels (17.0 to 25.6%) in the diets, whereas Newkirk and Classen (2001) reported that purified phytase improved the ileal AA digestibility of broilers fed diets containing pretreated CM. In view of the dearth of data, the current study was designed to determine the effect of phytase supplementation on ileal digestibility of AA and protein utilization in CM for broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been used to correct this underestimated digestibility in poultry (Adedokun et al, 2007), with each of these methods having some advantages and disadvantages. Rodehutscord et al (2004) suggested that the regression method could be used to estimate ileal AA digestibility without separate determination of endogenous AA losses in broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid contents in the RSM and in the 8 and 16 h in situ incubation residues were measured with an amino acid analyser L8900 (VWR/Hitachi). After oxidation with performic acid, samples were hydrolysed with 6 M HCl for 24 h at 1108C (Rodehutscord et al, 2004). The AA were separated with ion-exchange chromatography and quantified by post-column derivatisation with ninhydrin using photometric detection at 570 nm (440 nm for proline).…”
Section: Analytical Proceduresmentioning
confidence: 99%